A idade da menopausa é associada com a função física? uma revisão sistemática - Macêdo, Pedro Rafael de Souza (2020)
Introduction: Menopause at an early age increases the time of exposure to the negative effects of hypoestrogenism on the female aging process.It is well established that early menopause is associated with osteoporosis, chronic diseases and mortality. Although it is recognized that there is a greater decline in physical function in women after menopause, the association between early menopause and measures of physical function is not well established.Objective: To assess the association between early menopause and different measures of physical function and the importance of the socioeconomic context in this association.Methods: Systematic review of observational studies in the PubMed, Cochrane Library, SciELO, LILACS and Web of Science databases. Studies that assessed the association between early menopause and measures of physical function were included, with no restriction on the period of publication or language.To assess the methodological quality of the studies, the “Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies” was used.Results: Four studies were included, all cross-sectional, totalizing 13,846 participants, and that investigated five measures of physical function (handgrip strength, gait speed, standbalance, chair standsand self-reported functional limitation).The 4 studies evaluated populations from developed countries and only one also included samples from developing countries. All studies reported an association between some measure of physical function and premature (<40 years) or early (<45 years) menopause, whether natural or surgical.The measures that were associated with the age atmenopause were the handgrip strength (found in 2 of the 3 studies that evaluated this measure), being between 2.58 kg (95% CI=0.74; 4.43) and 5.21 kg (2.18; 8.25) weaker among women with menopause <40 years; gait speed (found in 2 of the 3 studies that evaluated this measure) with results between 0.03 m/s (0.01; 0.06) and 0.06 m/s (0.02; 0.09) slower between those with menopause <40 and <45 years;and self-reported functional limitation (assessed in only one study), with women with menopause after 50 years of age presenting lower chances compared to those who had menopause <40 or <45years (OR between 0.52 [95% CI=0.29; 0.95] and 0.61 [0.40; 0.95]).Two measures of physical function, the chair standstest and standbalance, were not significantly associated with age at menopause.Due to the great heterogeneity among the studies in relation to the classification of the menopausal age groups, it was not possible to perform the meta-analysis.Conclusion: There is some evidence of an association between menopause at younger ages and worse physical function.Women who experience menopause at younger ages should be screened earlier and more frequently for functional impairmentand encouraged to participate in physical rehabilitation programs.Further studies are needed to explore the association between age at menopause and different measures of physical function using standardized measures for early menopause identification and longitudinal methodologies.In addition, further studies are needed to assess the influence of different socioeconomic contexts on functionality